Employing social constructionism to deconstruct how 'disabled learners' and 'delinquent students' are managed within the education system: could social scientists play a moral role? / Airil Haimi Adnan - Adnan, Airil Haimi (2002)
This paper describes Social Constructionism as a post-modern approach to understanding the ever changing nature of our social world. Social constructionists accept the existence of biological reality, but they are critical of how socio-cultural knowledge is shared and disseminated through our 'common sense' notion of what is natural, inevitable and unproblematic. The language we use and the labels we adopt as part of our common sense, have all led to the creation of the subject-position of 'otherness' - People who are seen as having problems, and are themselves seen as problems to be managed. The realm of formal Education was chosen to illustrate this reality further, by unpacking and critically examining (he labels 'disabled learners' and 'delinquent students', to show how our common sense have had material effects on the real lives of these 'others '. Disability and delinquency are not just given labels, they govern our perception and understanding of socio-physical reality. Through the mass media and popular culture, common sense perceptions of these labels have been perpetuated and reinforced until drastic measures are taken at policy level to manage learners who are disabled and those who are considered to be undisciplined and delinquent. This presents a challenge for social scientists in Malaysia, and other nation-states in the world. How could they playa moral role and challenge the dangers of common sense knowledge? Social scientists must ensure that every member of society is shown alternative projections of the world that could reflect and represent social reality and contemporary life as they really are, as a concerted effort against our limited common sense 'knowledge' of everything.